(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: Nurses in intensive care units (ICUs) face a demanding work environment that may lead to heightened stress and anxiety. This study aimed to assess the relationship between stress and anxiety among ICU nurses at Nishtar Hospital, Multan. Methods: A cross-sectional correlational study was conducted over a three-month period with 50 ICU nurses selected through purposive sampling. Data were collected using the Perceived Stress Scale (PSS-10) and the Generalized Anxiety Disorder Scale (GAD-7). Descriptive statistics and Pearson’s correlation analysis were performed using SPSS v26. Results: The majority of participants were female (86%) with a mean age of 30.2±5.6 years. Moderate to high stress levels were found in 68% of nurses, while 48% reported moderate to severe anxiety symptoms. Pearson’s correlation revealed a significant positive relationship between stress and anxiety (r=0.62, p<0.001). Conclusion: Stress and anxiety are prevalent among ICU nurses, and the significant correlation between them indicates that interventions addressing occupational stress may also help reduce anxiety symptoms. Institutional support, stress management training, and workload adjustments are recommended.